Phytotelmata colonization in bamboo (Guadua sp.) culms in northeast Argentina - Campos, Raúl Ernesto (2016)
This study aimed to determine the susceptibility of stumps and internodes of bamboos to colonization by different types of macroinvertebrates and the formation of communities of different complexity. Semi-controlled field studies were carried out in a subtropical area of Argentina to analyse community structure, species richness of the aquatic macroinvertebrate communities and co-occurrences of predators and prey to delineate the food webs. Water-filled bamboos were sampled every season during a year by removing, without replacing, all water and macroinvertebrates. This study shows that the variation in the morphology of the container provides different resources, leading to segregation of species per container type, and allowing each of them to establish aquatic communities with differences in diversity. The Diptera was best represented in the communities of bamboos, where Culicidae showed the highest species richness and Ceratopogonidae were the most abundant numerically. Eleven taxa were present in both phytotelmata, 12 were unique in internodes and 13 in stumps. The community in internodes was composed of 21 taxa where mosquitoes were represented by Sabethini and Toxorhynchitini. By contrast, stumps were colonized by 24 taxa and Ceratopogonidae were numerically dominant. Regarding food webs established in stumps and internodes, no differences in length were found, except for the species that played equivalent roles in each of the studied phytotelmata.